Modelling and simulation of a moving interface problem: freeze drying of black tea extract - Aydin, Ebubekir Siddik; Yucel, Ozgun; Sadikoglu, Hasan (SPRINGER, 2017)
The moving interface separates the material that is subjected to the freeze drying process as dried and frozen. Therefore, the accurate modeling the moving interface reduces the process time and energy consumption by improving the heat and mass transfer predictions during the process. To describe the dynamic behavior of the drying stages of the freeze-drying, a case study of brewed black tea extract in storage trays including moving interface was modeled that the heat and mass transfer equations were solved using orthogonal collocation method based on Jacobian polynomial approximation. Transport parameters and physical properties describing the freeze drying of black tea extract were evaluated by fitting the experimental data using Levenberg-Marquardt algorithm. Experimental results showed good agreement with the theoretical predictions.
Keywords: FINITE-ELEMENT-ANALYSIS; PARAMETER-ESTIMATION; TRAYS; PRODUCTS; VIALS; Thermodynamics; Mechanics